Characterization of deep level defects in Tl6I4S single crystals by photo-induced current transient spectroscopy. (2nd February 2015) - Peters, J A; Liu, Z; Im, J; Nguyen, S; Sebastian, M; Freeman, A J; Kanatzidis, M G; Wessels, B W
Abstract: Defect levels in semi-insulating Tl6 I4 S single crystals grown by the horizontal Bridgman technique have been characterized using photo-induced current transient spectroscopy (PICTS). These measurements revealed six electron traps located at (0.059  ±  0.007), (0.13  ±  0.012), (0.31  ±  0.074), (0.39  ±  0.019), (0.62  ±  0.110), and (0.597  ±  0.105). These defect levels are attributed to vacancies (V I, V S ) and antisite defects (I S, Tl S, Tl I ) upon comparison to calculations of native defect energy levels using density functional theory and defects recently reported from photoluminescence and photoconductivity measurements.